Environmental impact of production and use of geothermal energy in Ukraine - Лимаренко, Алексей Николаевич; Тараненко, Олеся Александровна (Technology audit and production reserves, 2015)
General potential of geothermal resources of Ukraine and the possibilities of their use as an alternative fuel are considered in the article. The most promising regions of Ukraine for the development of geothermal energy were determined and the characteristics of the heat-transfer agent were described. Value engineering analysis of modern technologies of extraction of heat was carried out, taking into account a feasibility study. Possibilities of using depleted oil and gas fields were studied, as well as the simultaneous use of wells for the extraction of hot water and hydrocarbons. The factors that affect the extent of the use of geothermal energy were examined. The important aspects of the use of geothermal energy sources, such as renewability, getting a heat-transfer agent of much lower temperature than from firing, combination of the energy use and minimal detrimental impact on the environment were listed. There were also described the disadvantages of use of geothermal resources, such as the need to use at the place of production, the high cost of construction of wells with increased depth, swamping the area, release into the atmosphere of dissolved sulfur compounds, mercury, arsenic and boron. Methods to reduce harmful emissions into the environment of geothermal power plants were proposed.